2021
DOI: 10.1029/2021gl093309
|View full text |Cite
|
Sign up to set email alerts
|

Upper Mantle Hydration Indicated by Decreased Shear Velocity Near the Southern Mariana Trench From Rayleigh Wave Tomography

Abstract: The properties of incoming oceanic plates, such as their geometry and water content closely influence various processes in subduction zones, including the generation of earthquakes and arc magmatism (Grove et al., 2009;Shillington et al., 2015). Water content is especially important because water transported by the incoming plate cools the subduction zone, promotes forearc metamorphism, and facilitates the generation of arc magmatism (Fujie et al., 2016;Hyndman & Peacock, 2003). Since the subducting slab is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 47 publications
6
36
0
Order By: Relevance
“…If plate rupture occurs, a positive fault is created, which can be observed by earthquake localization. Seismic velocity models obtained from previous surface wave imaging results show a significant low-velocity anomaly in the subducted slab that extends to a depth of about 25 km inside the mantle, indicating that the southern Marianas subducted slab carries a large amount of water into the Earth's interior (Zhu et al, 2021). Compared with central Mariana (Kato et al, 2003), the velocity reduction of the southern arc-front mantle is not as obvious, suggesting that the degree of serpentinization of the arc-front mantle is lower in the south.…”
Section: Resultsmentioning
confidence: 92%
“…If plate rupture occurs, a positive fault is created, which can be observed by earthquake localization. Seismic velocity models obtained from previous surface wave imaging results show a significant low-velocity anomaly in the subducted slab that extends to a depth of about 25 km inside the mantle, indicating that the southern Marianas subducted slab carries a large amount of water into the Earth's interior (Zhu et al, 2021). Compared with central Mariana (Kato et al, 2003), the velocity reduction of the southern arc-front mantle is not as obvious, suggesting that the degree of serpentinization of the arc-front mantle is lower in the south.…”
Section: Resultsmentioning
confidence: 92%
“…For example, Z. Zhou et al. (2015) conducted 2‐D elastoplastic modeling and suggested that the maximum depth extent of outer‐rise normal faults in the trench was around 30 km below the seafloor, close to the depth of serpentinization within the incoming plate that was inferred from tomographic results (G. Zhu et al., 2021). The focal depths of extensional earthquakes have also been used as indicators.…”
Section: Introductionmentioning
confidence: 98%
“…Incoming plates at subduction zones are the major regions where water can be transferred into the Earth's depths. Estimating the degree of hydration of the incoming plates usually requires high‐resolution tomographic images based on near‐field observations (Cai et al., 2018; Fujie et al., 2013; Shillington et al., 2015; Van Avendonk et al., 2011; G. Zhu et al., 2021). Since the outer‐rise normal faults serve as pathways for water penetrating into the oceanic plate before subduction (Grevemeyer et al., 2007; Ivandic et al., 2010; Peacock, 2001; Ranero et al., 2003), the depth extent of outer‐rise normal faults has been regarded as a good indicator of the water input in the subduction zones.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plate bending may cause active trench-parallel normal faulting, providing important pathways for seawater to hydrate the incoming plate (e.g., Cabrera et al, 2021;Cai et al, 2018;Zhang et al, 2021;Zhou et al, 2015;Zhu et al, 2021) and generating tensional earthquakes at outer rise. A thin plate model was most often used to investigate the plate deflection and bending stress, and the corresponding outer rise intraplate earthquakes (Garcia-Castellanos et al, 2000;Watts, 2001;Contreras-Reyes & Osses, 2010;Emry et al, 2014;Zhou et al, 2015Zhang et al, 2014;.…”
mentioning
confidence: 99%